2007
DOI: 10.1016/j.patcog.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Translation and scale invariants of Tchebichef moments

Abstract: Abstract⎯Discrete orthogonal moments such as Tchebichef moments have been successfully used in the field of image analysis. However, the invariance property of these moments has not been studied mainly due to the complexity of the problem. Conventionally, the translation and scale invariant functions of Tchebichef moments can be obtained either by normalizing the image or by expressing them as a linear combination of the corresponding invariants of geometric moments. In this paper, we present a new approach th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 22 publications
0
41
0
2
Order By: Relevance
“…In this context, radial Tchebichef moments were proposed to obtain rotation invariant descriptors from images [42]. Additionally, translation and scale invariants from DTM have been defined [43].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, radial Tchebichef moments were proposed to obtain rotation invariant descriptors from images [42]. Additionally, translation and scale invariants from DTM have been defined [43].…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach was then used to construct both translation and scale invariants of Legendre moments [4]. The problem of scale and translation invariants of Tchebichef moments has been investigated by Zhu et al [43]. Discrete orthogonal moments such as Tchebichef moments yield better performance than the continuous orthogonal moments, but the rotation invariants are dicult to derive.…”
Section: Derivation Of Moment Invariants To Geometric Transformationsmentioning
confidence: 99%
“…To overcome this shortcoming, Mukundan [19] introduced the radial Tchebichef moments, which are dened in polar coordinate system, to achieve the rotation invariance. It was shown that the methods reported in [3,4,43,19] perform better than the classical approaches such as image normalization and indirect methods. However, it seems dicult to obtain the completeness property by the above mentioned methods since no explicit formulation is derived for moment invariants.…”
Section: Derivation Of Moment Invariants To Geometric Transformationsmentioning
confidence: 99%
“…Mainly, two methodologies used to ensure invariance under common geometric transformations such as rotation, scaling and translation, either by image coordinates normalization and description through the geometric moment invariants (Mukundan & Ramakrishnan, 1998;Zhu et al, 2007) or by developing new computation formulas which incorporate these useful properties inherently (Zhu et al, 2007).…”
Section: Invariant Descriptionmentioning
confidence: 99%